Transient complex I inhibition at the onset of reperfusion by extracellular acidification decreases cardiac injury - Xu, Aijun (American Physiological Society, 2014)
A reversible inhibition of mitochondrial respiration by complex I inhibition at the onset of reperfusion decreases injury in buffer-perfused hearts. Administration of acidic reperfusate for a brief period at reperfusion decreases cardiac injury. We asked if acidification treatment decreased cardiac injury during reperfusion by inhibiting complex I. Exposure of isolated mouse heart mitochondria to acidic buffer decreased the complex I substrate-stimulated respiration, whereas respiration with complex II substrates was unaltered. Evidence of the rapid and reversible inhibition of complex I by an acidic environment was obtained at the level of isolated complex, intact mitochondria and in situ mitochondria in digitonin-permeabilized cardiac myocytes. Moreover, ischemia-damaged complex I was also reversibly inhibited by an acidic environment. In the buffer-perfused mouse heart, reperfusion with pH 6.6 buffer for the initial 5 min decreased infarction. Compared with untreated hearts, acidification treatment markedly decreased the mitochondrial generation of reactive oxygen species and improved mitochondrial calcium retention capacity and inner mitochondrial membrane integrity. The decrease in infarct size achieved by acidic reperfusion approximates the reduction obtained by a reversible, partial blockade of complex I at reperfusion. Extracellular acidification decreases cardiac injury during reperfusion in part via the transient and reversible inhibition of complex I, leading to a reduction of oxyradical generation accompanied by a decreased susceptibility to mitochondrial permeability transition during early reperfusion.